Description of Test Model Development and Testing Results Literacy Contextualized Text Information Biology Assessment Competency - ridlo, saiful (Universitas Negeri Semarang, 2024)
This article describes the results of an analysis of biology learning achievement testing for class X high school students using Minimum Competency Assessment (AKM) model questions to measure literacy in reading scientific texts in a biological context. The research was conducted in the FMIPA UNNES Community Service series with a sample of 185 students from various high schools in Central Java. A total of 15 questions with a biological context were taken from the AKM question collection on the page https://pusmendik.kemdikbud.go.id/ and assembled in a Google form. Student responses were analyzed using the Rasch model with Winstep 5.2.2.0. The results of the analysis show that the questions used fit based on the MNSQ and PT Measure Corr values, or it can be interpreted that all the question items are valid. The question set is also estimated to be reliable because it meets Cronbach's Alpha value in the sufficient category. The item reliability value for measuring the quality of the questions is estimated to be adequate, and even the reliability value for measuring students' consistency in answering is estimated to be excellent. The sample of students can be classified into the literate group reading scientific information texts requiring particular intervention, basic, proficient, and proficient, with the most significant proportion being the proficient group.